RELIABILITY OF THE CONTROL OF ELECTRONIC DEVICES BY LOW-FREQUENCY NOISE - MYKHALEVSKIY, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article examines the stages of input and output control of electronic equipment products according to the level of their own low-frequency noise, namely, the measurement of an informative parameter and its comparison with predetermined limits. It was established that for each type of control there is a need to have a methodology for assessing the compliance of control results with valid characteristics and its effectiveness. One of the main parameters of the effectiveness of all stages of control is the probability, which requires separate studies and the definition of a universal mechanism for its assessment. Therefore, the task was set to obtain a complete method of probability assessment for the input and output control of electronic equipment products by the level of their own noise. To determine the probabilistic characteristics of the control, the main informative parameters were investigated: the measuring noise voltage, which is random in nature, and the random error. It is established that the measured value has a confidence interval that takes into account measurement errors and determination of control limits. Control limits were obtained, on the basis of which analytical expressions were obtained for the distribution of the informative parameter within the specified limits for reliable and unreliable electronic products. Taking into account the limit of separation of products into suitable and unsuitable, control limits were proposed, which contain the coefficient of possible error cut-off. A generalized analytical expression for evaluating the probability of control is obtained, which takes into account the minimization of the effect of systematic and random factors influencing the result to increase the efficiency of input and output control on the level of low-frequency noise.